2007
DOI: 10.1017/s0022215107006226
|View full text |Cite
|
Sign up to set email alerts
|

Visual loss in the setting of allergic fungal sinusitis: pathophysiology and outcome

Abstract: Objective: To hypothesise the probable pathophysiological mechanism responsible for visual loss in allergic fungal sinusitis, other than direct compression.Design: Retrospective, non-randomised case series. Out of 274 cases of allergic fungal sinusitis, four cases with sudden visual loss were enrolled into the study. The fourth case had visual loss on the contralateral side to bony erosion of the lateral wall of the sphenoid sinus.Interventions: All four cases were evaluated with fungal smear, immunoglobulin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Optic neuritis due to the inflammatory process and critical retinal artery occlusion seem to be the underlying factors responsible for sudden vision loss in AFRS. This is supported by the fact that Thakar et al [10] and Gupta and colleagues [7] reported good recovery of vision in cases of sudden or recent onset visual loss after surgical decompression and steroid use.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Optic neuritis due to the inflammatory process and critical retinal artery occlusion seem to be the underlying factors responsible for sudden vision loss in AFRS. This is supported by the fact that Thakar et al [10] and Gupta and colleagues [7] reported good recovery of vision in cases of sudden or recent onset visual loss after surgical decompression and steroid use.…”
Section: Discussionmentioning
confidence: 81%
“…Ophthalmic manifestations range from proptosis most commonly [9,13] to vision loss in extreme cases [7][8][9][10]. Vision loss is an extremely uncommon complication of AFRS with either a sudden acute [7,10] or gradually progressive mode of presentation [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations